Lung volumes, ventilatory capacity, and transfer factor in healthy British boy and girl twins. Issue 6 (November 1973) - Cotes, J. E.; Dabbs, J. M.; Hall, A. M.; Axford, A. T.; Laurence, K. M.
Abstract : Cotes, J. E., Dabbs, J. M., Hall, A. M., Axford, A. T., and Laurence, K. M. (1973) . Thorax, 28, 709-715. Lung volumes, ventilatory capacity, and transfer factor in healthy British boy and girl twins . Normal values are reported for the lung volumes, ventilatory capacity, and transfer factor of 212 healthy British twin children aged 8 to 16 years. The boys and the girls share a common relationship to height for the residual volume, peak expiratory flow rate, and K co (transfer factor per litre of lung volume). For the inspiratory capacity and the transfer factor, also its membrane component ( D m), the values for the boys exceed those for the girls by, on average, 10%. This difference may be due, at least in part, to the boys taking more exercise.